Pendampingan Penanaman Kembali Hidroponik Di Taman Balai Desa Banjarsari - Tholib Hariono; Nur Faisal Andani; Anggi Indah Yuliana; Anton Muhibuddin (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2021)
The objectives of this service activity include replanting hydroponic plants in the yard of Banjarsari Village Hall through cleaning weeds around hydroponics, cleaning hydroponic equipment, hydroponic education. The approach method for implementing community service activities includes discussion and practice methods. The results of this service include; Replanting is carried out into hydroponic cultivation in the yard, hydroponic replanting can provide a view of plants at the Banjarsari village hall, Hydroponic cultivation education for teenagers can create positive activities that can be carried out in a sustainable manner.